Root functioning, tree water use and hydraulic redistribution in Quercus suber trees: A modeling approach based on root sap flow - David, Teresa S.; Pinto, Clara A.; Nadezhdina, Nadezhda; Kurz-Besson, Cathy; Henriques, Manuel O.; Quilhó, Teresa; Čermák, Jan; Chaves, M. Manuela; Pereira, João S.; David, Jorge S. (Forest Ecology and Management, 2013)
Mediterranean evergreen oaks have to survive a long summer drought. Roots may play a relevant role under these conditions. We studied their structure and function in a mature Quercus suber L. tree in central Portugal. The root system was mapped till the lowest water table level (4.5 m depth). Xylem anatomy was analyzed in a vertical profile belowground. Sap flow was continuously monitored for 1.5 yrs in the stem and roots of this intensively studied tree (heat field deformation method) and in the stem of four trees (Granier method), in relation to environmental variables and predawn leaf water potential. The sources of water uptake were assessed by stable isotope analyses in summer. Results showed a dimorphic root system with a network of superficial roots linked to sinker roots, and a taproot diverting into tangles of deep fine roots submerged for long periods, with parenchyma aerenchyma. Transpiration was not restricted in summer due to root access to groundwater. The isotopic δ18O signature of twig xylem water was similar to that of groundwater in the dry season. Two functional types of superficial roots were identified: shallow connected and deep connected roots. A modeling approach was built considering that each superficial root was linked to a sinker, with part of the root deep connected (between the stem and the sinker) and part shallow connected (between the sinker and topsoil). This conceptual framework simulated tree stem sap flow from root sap flow with a high efficiency (R2 = 0.85) in four plot trees. On an annual basis, soil water and groundwater contributions were 69.5% and 30.5% of stem flow, respectively. Annual hydraulic lift and hydraulic descent were 0.9% and 37.0% of stem flow, respectively. The trees maximize the exploitation of the environmental resources by using the topsoil water during most of the year, and groundwater together with hydraulic lift (nutrient supply) in the dry summer. This study shows that a dimorphic root system, with roots reaching groundwater, is an efficient strategy of Q. suber trees to cope with seasonal drought. Knowledge of the functional behavior of Q. suber trees under shallow water table conditions may contribute to the definition of better adapted management practices and to anticipate their responses to climate change.
Keywords: Drought; groundwater; soil water; Stable isotopes; xylem anatomy

Transpiration in Quercus suber trees under shallow water table conditions: the role of soil and groundwater (Hydrological Processes, 2013)
Water is one of the major environmental factors limiting plant growth and survival in the Mediterranean region. Quercus suber L. woodlands occupy vast areas in the Iberian Peninsula, frequently under shallow water table conditions. The relative magnitude of soil and groundwater uptake to supply transpiration is not easy to evaluate under these circumstances. We recently developed a conceptual framework for the functioning of the root system in Q. suber that simulates well tree transpiration, based on two types of root behaviour: shallow connected and deep connected. Although this significantly improved knowledge on the functional traits of Mediterranean Q. suber, the approach has the limitation of requiring root sap flow data, which are seldom available. In this work, we present alternative methodologies to assess if trees are connected to groundwater and to estimate the soil and groundwater contributions to tree transpiration. We provide evidence on the tree unrestricted access to groundwater solely based on meteorological, stem sap flow and leaf water potential data. Using a soil mass balance approach, we estimated the yearly soil and groundwater contributions to tree transpiration: 69.7% and 30.3%, respectively. Groundwater uptake became dominant in the dry summer: 73.2% of tree transpiration. Results reproduce extremely well those derived from root modelling. Because of its simplicity both in formulation and data requirements, our approach is potentially liable to be adapted to other groundwater- dependent Mediterranean oak sites, where interactions between land use and water resources may be relevant.